Constraints and enablers of poultry farming on the rural women’s empowerment in Sabon Gari Local Government Area of Kaduna State, Nigeria - Akorede, Ibrahim Ayinla; Njidda, Dahiru Kobru; Ogwuche, Abubakar Sidiq (UIR Press, 2025)
Purpose: This paper investigates the constraints and enablers of poultry farming on the rural women’s empowerment in Sabon Gari Local Government Area of Kaduna State, Nigeria. Design/methodology/approach: The study selected a sample of 256 women farmers through a simple random sampling. Structured questionnaires were used to gather data. Regression analysis was utilized for hypothesis testing. Findings: The study identified gender-based discrimination, obsolete technology, insufficient capital access, and market access as the main constraints. The results show that poultry farming promotes women's participation in family and community decision-making, enhances their ability to cover home expenses, and helps them achieve financial sustainability. Limitations and Research Implications: The study is limited to modern factors influencing the participation of rural women in poultry farming. This stimulates further research interest in understanding the influence of women’s involvement in agriculture on their standard of living, fostering a broader dialogue on rural women’s empowerment through farming practices in Kaduna State and Nigeria as a whole. Practical Implications: The findings of this study will be valuable to the Kaduna state Ministry of Agriculture, the NGOs, and Agricultural Extension Services in Kaduna state to gain insight into strategies to support women farmers in achieving greater productivity, provide women farmers with adequate inputs and services, and improve female extension services with strategies to reduce poverty. Originality/Value: The study posited that poultry farming is a critical tool for empowering rural women despite their challenges, addressing key constraints, and enhancing access to capital and technical resources. Despite these challenges, poultry farming remains a viable livelihood strategy for rural women due to its low startup costs and high turnover rate.